The effect of salt concentration on the color, texture and sensory analysis of beefballs / Megat Mohamad Shahril Adnan - Adnan, Megat Mohamad Shahril (2003)
Four formulations of beef balls were studied by varying the salt concentration from 1.5% to 3%. The following evaluations were performed on the beef ball. Texture Profile Analysis, color and sensory analysis. Texture parameters analyzed were cutting strength, firmness and springiness. Beef ball with 2.5% salt concentration is the most firm, most springy and has the highest cutting strength compared to other formulations. The values for firmness, springiness, cutting strength are 390.3, 57.6 and 799.2 respectively. Colour measurements were measured by using CIE color lab. For the color , "a" are significantly different, but "L" and "b" values, there are no significantly different among the formulations. The "a" value for all formulations (varying the salt concentration from 1.5% to 3%) ranged from -2.1 to -0.7. Preference test by using 9 hedonic scales was used in sensory evaluation. . The mean for taste of all formulations range from 5.5 to 6.4. All the data were analyzed and evaluated by using the Statistical Analysis System (SAS). However, the varying of salt concentration does not significantly affect the sensory properties except taste. Furthermore, the beef ball with 2.5% salt concentration had the highest acceptabihty values than other three formulations. It is most preferred for colour, taste and overall acceptabihty.